Neuroimaging Spectrum of Erdheim-Chester Disease: An Image-Based Review - Rai, Pranjal; Swartz, Hayden J.; Soni, Neetu; Benson, John C.; Agarwal, Amit; Messina, Steven A.; Farnsworth, Paul J.; Carr, Carrie M.; Bathla, Girish (American Journal of Neuroradiology, 2025)
SUMMARY: Erdheim-Chester disease (ECD) is a rare, multisystem histiocytic disorder characterized by its variable clinical presentations. CNS involvement is observed in approximately one-half of patients with ECD (up to 76% in some series) and often carries a poorer prognosis. While CNS involvement may remain asymptomatic, others may experience a range of neurologic symptoms, including cognitive decline, neuropsychiatric disturbances, motor deficits, cranial or peripheral neuropathies, and endocrine abnormalities. Neuroimaging findings in CNS-ECD are diverse, including neurodegeneration manifesting as cerebral or cerebellar volume loss; solitary or multifocal variably enhancing intraparenchymal lesions along the neuroaxis; meningeal infiltration; and involvement of the hypothalamo-pituitary axis, perivascular sheathing, or basal ganglia lesions. Other well-documented sites of involvement include the craniofacial region, orbits, and spine. Awareness of these findings is relevant, not only because of the nonspecific nature of these findings, but also because of the high proportion of CNS involvement in ECD and the higher mortality associated with CNS involvement. This review provides an in-depth overview of the various manifestations of CNS involvement in ECD and their imaging features, along with a brief overview of the differential considerations, which include other histiocytic and nonhistiocytic processes.CEcontrast-enhancedCLIPPERSchronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroidsECDErdheim-Chester diseaseGWPgranulomatosis with polyangiitisHPAhypothalamo-pituitary axisLCHLangerhans cell histiocytosisMAPKmitogen-activated protein kinaseMEKmitogen-activated protein kinase kinaseRDDRosai-Dorfman disease